Soil salinity under climate change: Challenges for sustainable agriculture and food security. (15th February 2021) - Mukhopadhyay, Raj; Sarkar, Binoy; Jat, Hanuman Sahay; Sharma, Parbodh Chander; Bolan, Nanthi S.
Abstract: Soil salinity is one of the major and widespread challenges in the recent era that hinders global food security and environmental sustainability. Worsening the situation, the harmful impacts of climate change accelerate the development of soil salinity, potentially spreading the problem in the near future to currently unaffected regions. This paper aims to synthesise information from published literature about the extent, development mechanisms, and current mitigation strategies for tackling soil salinity, highlighting the opportunities and challenges under climate change situations. Mitigation approaches such as application of amendments, cultivation of tolerant genotypes, suitable irrigation, drainage and land use strategies, conservation agriculture, phytoremediation, and bioremediation techniques have successfully tackled the soil salinity issue, and offered associated benefits of soil carbon sequestration, and conservation and recycling of natural resources. These management practices further improve the socio-economic conditions of the rural farming community in salt-affected areas. We also discuss emerging reclamation strategies such as saline aquaculture integrated with sub surface drainage, tolerant microorganisms integrated with tolerant plant genotypes, integrated agro-farming systems that warrant future research attention to restore the agricultural sustainability and global food security under climate change scenarios. Graphical abstract: Image 1 Highlights: Distribution, causes and climate change vulnerability of salt-affected soil highlighted. Management strategies of salt-affected soil under climate change discussed. Socioeconomic and environmental impacts of management strategies reviewed. Different innovative reclamation strategies warrant future research.